2014
DOI: 10.1016/j.jval.2014.03.1277
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with performance on the medicaid hedis measure: Continuity of antipsychotic (AP) medications for treatment of schizophrenia

Abstract: Objectives: To develop an economic model that estimates the cost burden of psychiatric relapse and recidivism among patients with schizophrenia after release from jail/prison from a US state government perspective. MethOds: A Markov state-transition model was developed to estimate the numbers of schizophrenia patients newly-released from jail/prison who would experience psychiatric relapse and/or arrest and re-incarceration over a period of three years, along with corresponding costs. The model includes three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…One study indicated Hispanics had greater adherence to paliperidone palmitate (1-month LAI) compared with other antipsychotics. 37 However, the study mixed oral and other LAI antipsychotics into one group, thereby limiting the results as oral and LAI agents may carry different adherence rates.…”
Section: Discussionmentioning
confidence: 99%
“…One study indicated Hispanics had greater adherence to paliperidone palmitate (1-month LAI) compared with other antipsychotics. 37 However, the study mixed oral and other LAI antipsychotics into one group, thereby limiting the results as oral and LAI agents may carry different adherence rates.…”
Section: Discussionmentioning
confidence: 99%
“…1 Despite the need for continuous drugs treatment, medication compliance remains a critical issue in schizophrenia, with non-adherence rates ranging from 34% to 81%. [2][3][4][5][6][7][8] Antipsychotics non-adherence leads to a greater risk of relapses and negative overall outcomes. 9,10 Several factors, such as lack of insight, comorbid disorders (substances use and depressive symptoms), side effects, cognitive impairment and high hostility levels, can play a role in medication nonadherence in schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…Psychotic symptoms usually respond to antipsychotic medications, which are also used for long-term maintenance and prevention (Kane and Correll, 2019). Yet, according to research, due to a multitude of factors, 34–81% of patients discontinue their antipsychotic medications with many studies putting the rate around 50% (Yang et al, 2012; El-Mallakh and Findlay, 2015; García et al, 2016; Lafeuille et al, 2016; Bright, 2017; De Las Cuevas et al, 2017; Velligan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%